Halal Industry during the Covid-19 Pandemic is The Hidden Blessing: Industri Halal Selama Pandemi Covid-19 Adalah Berkah Tersembunyi - yudha, Ana Toni Roby Candra; Kafabih, Abdullah (Islamic Economic Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2021)
The MSMEs-based halal industry is one of the sources that should be taken into account to be developed. This study aims to provide a comprehensive review and analysis of the halal industry and micro, small and medium enterprises (MSMEs) in their efforts to maintain economic resilience during a Covid 19 pandemic. This analysis focuses on theoretical, established and empirical reviews that focus on the halal industry as a new fiscal source. This study uses a literature study review approach for the halal industry from various literature on the halal industry and MSMEs from Indonesia and overseas. The literature is also limited to the publication of 2015-2020. The findings of this study are that halal industry is the newest source of Islamic economics that can be relied on in raising the country's fiscal. Of course, it is intended for poverty alleviation, distribution of consumption, public service media and other relevant instruments. However, the halal industry integration system can become a